2010
DOI: 10.1177/1359105310378180
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Adherence to Antiretroviral Treatment

Abstract: Patient advocates were asked for their perspectives on the structural barriers to adherence to antiretroviral treatment among patients living with HIV. Poverty-related barriers were transport difficulties, food insecurity and patients' receipt of a disability grant. Institutional barriers were long waiting times at clinics, negative experiences with clinic staff, low levels of health literacy and poor access to substance abuse treatment. Social and cultural barriers were the role of traditional healing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Our data and that from other groups underscore the critical need to address structural barriers related to poverty, including HIV treatment cost (in settings where ART is not free of charge), food insecurity, and lack of transport money to attend the clinic, as well as health care facility-related factors such as pharmacy stock outs. [26][27][28][29][30][31] On the other hand, previously reported social-related barriers to ART adherence such as HIV status nondisclosure and stigma [32][33][34][35][36] were reported among our study participants in all regions.…”
Section: Discussionmentioning
confidence: 54%
“…Our data and that from other groups underscore the critical need to address structural barriers related to poverty, including HIV treatment cost (in settings where ART is not free of charge), food insecurity, and lack of transport money to attend the clinic, as well as health care facility-related factors such as pharmacy stock outs. [26][27][28][29][30][31] On the other hand, previously reported social-related barriers to ART adherence such as HIV status nondisclosure and stigma [32][33][34][35][36] were reported among our study participants in all regions.…”
Section: Discussionmentioning
confidence: 54%
“…The findings on religiosity echo reports from prior studies conducted among HIV-infected persons in SSA, where religion, especially Pentecostalism, was associated with increased psychological distress due to moralizing and/or discriminatory attitudes within religious congregations (Otolok-Tanga, Atuyambe, Murphey, Ringheim, & Woldehanna, 2007). For example, in a study conducted among adults living with HIV in South Africa found that Pentecostal religious beliefs were associated with HIV-stigma, leading to psychological distress, and also interfered with respondents' adherence to ART (Kagee & Delport, 2010). These findings allude to the diversity within religious denominations, and underscore the need to build interventions that, first, acknowledge differences within religious institutions and secondly, map onto the belief systems of these religious institutions, in order to mitigate any deleterious effects within these institutions.…”
Section: Discussionmentioning
confidence: 97%
“…Poor HIV-related knowledge is a structural barrier which, to a large extent, is a consequence of living in a resource-constrained environment (Kagee and Delport 2010). Guinea-Bissau is one of the poorest countries in the world.…”
Section: Discussionmentioning
confidence: 99%